2016
DOI: 10.1117/1.jbo.21.6.066001
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical microscopy for quantification of depth-dependent epithelial backscattering in the cervix

Abstract: Abstract. A fiber optic imaging approach is presented using structured illumination for quantification of almost pure epithelial backscattering. We employ multiple spatially modulated projection patterns and camera-based reflectance capture to image depth-dependent epithelial scattering. The potential diagnostic value of our approach is investigated on cervical ex vivo tissue specimens. Our study indicates a strong backscattering increase in the upper part of the cervical epithelium caused by dysplastic micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…In this regard, combinations with other techniques which feature an increased penetration depth or provide an additional form of contrast may add to the merits of cervical endomicroscopy. 29,30 This could allow for even better and more intuitive discrimination of the presented four diagnostic categories including moderate level precancers (CIN 2) and potentially also AIS.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, combinations with other techniques which feature an increased penetration depth or provide an additional form of contrast may add to the merits of cervical endomicroscopy. 29,30 This could allow for even better and more intuitive discrimination of the presented four diagnostic categories including moderate level precancers (CIN 2) and potentially also AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance to diagnostic imaging, it was recently shown that HSF can reveal superficial structures that were previously not observable with diffuse wide‐field imaging . Bodenschatz et al used diffuse optical microscopy, a method very similar to HSF, to show that backscattering signals encode information about the architecture and microsctructure in cancerous and precancerous epithelial tissue. A recent imaging‐probe implementation of this technique was used for the examination of cervical tissue , while a contact dermoscope implementation was used for the observation of skin lesions .…”
Section: Introductionmentioning
confidence: 99%
“…Bodenschatz et al used diffuse optical microscopy, a method very similar to HSF, to show that backscattering signals encode information about the architecture and microsctructure in cancerous and precancerous epithelial tissue. A recent imaging‐probe implementation of this technique was used for the examination of cervical tissue , while a contact dermoscope implementation was used for the observation of skin lesions . The latter study proposed color rendering of HSF images to communicate scatter‐based contrast features in an intuitive manner, but the scientific or diagnostic importance of color‐based perception of scatter‐based spectral signals is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Image quality may also be improved in the future with enhanced suppression of internal specular reflections using a microscope objective designed for epi-illumination as well as a camera with higher dynamic range. Further studies are needed to confirm the sensitivity of DOM to high nuclear density in cancer [206].…”
Section: Diffuse Optical Microscopy (Dom)mentioning
confidence: 99%
“…In DOM, multiple laterally structured sinusoidal projection patterns are employed to quantify tissue light backscattering. Figure 7 shows the DOM [206].…”
Section: Diffuse Optical Microscopy (Dom)mentioning
confidence: 99%